Isolation and identification of multi-trait plant growth-promoting rhizobacteria from coastal sand dune plant species of Pohang beach - Moon, Yong-Sun; Ali, Sajid (Folia microbiologica, 2022)
Rhizobacteria are root-associated bacteria that influence plant growth by various direct and indirect mechanisms. In quest of efficient plant growth-promoting rhizobacteria (PGPR) with multiple plant growth-promoting traits, a total of 52 rhizobacterial isolates were isolated from the rhizospheric soil collected at Pohang beach, Republic of Korea. The bacterial isolates were evaluated in vitro for their plant growth-promoting traits like production of 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase, indole-3-acetic acid (IAA), siderophore, and phosphate solubilization activities. More than 28% of the isolates revealed all of the multi-trait plant growth-promoting activities, whereas 11.54% exhibited robust results for producing IAA, ACC deaminase, siderophore, and phosphate solubilization activities. Similarly, 36% isolates were capable for the production of IAA, siderophore, and ACC deaminase, while 32% revealed phosphate solubilization and siderophore production. The isolates with prominent multi-trait plant growth-promoting activities were identified based on 16S rRNA gene sequences and matched to Pseudomonas koreensis-(S4T10), Pseudomonas fluorescens-(S3B1), Serratia fonticola-(S1T1), Sphingobacterium multivorum-(S1B1), Brevundimonas vesicularis-(S1T13), and Arthrobacter sp.-(S2T9) with 99-100% similarity. Our results confirm that further evaluation of these PGPR (exhibiting multi-traits for plant growth promotion) is required on crop plants to reveal their pragmatic role under normal and abiotic stress conditions and add into the consortium of biofertilizers for sustainable agriculture.
Keywords: písek; siderofory; Biofertilizers; IAA; ACC deaminase; RNA, Ribosomal, 16S; Rhizobacteria; Sand; půdní mikrobiologie; Siderophore; Phosphates; PGPR; Plant Roots; Soil Microbiology; Siderophores; Pseudomonas fluorescens; kořeny rostlin; fosfáty; RNA ribozomální 16S